Development of Broodlac Placement-cum-Removal Tool - Prasad, Niranjan; Pandey, S K; Bhagat, M L (Journal of Agricultural Engineering, 2007)
Lac cultivation involves six major operations viz., pruning of lac host tree, selection of broodlac and bundle making, broodlac placement on host tree, used up broodlac removal, lac crop harvesting and lac scraping. The broodlac placement on the lac host tree is one of the important operations in lac cultivation, In traditional method, farmers use bamboo pole to hang broodlac stick on the branch of lac host trees. When broodlac stick hangs on the branch of the host tree, very small area of broodlac stick comes in contact with the branch of lac host tree. As a result tiny lac insects emerging from the broodlac gets narrow path for travel to the branches of the host tree in search of suitable shoot to settle down and start new life cycle. In improved method, farmers climb on the tree and tie prepared broodlac bundle on the branch of the host tree,just below pruning point. This method is laborious and time consuming. Therefore, a simple, easy to fabricate and low cost, broodlac placement-cum- removal tool was developed.